Molecularly imprinted polypyrrole film-coated poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate-functionalized black phosphorene for the selective and robust detection of norfloxacin. (December 2022) - Li, Guangli; Wu, Jingtao; Qi, Xiaoman; Wan, Xuan; Liu, Ying; Chen, Yuwei; Xu, Lijian
Abstract: An efficient molecularly imprinted polymer (MIP) voltammetric sensor was prepared based on polypyrrole (PPy) imprinted film-bearing poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate-functionalized black phosphorene (BP-PEDOT:PSS) for the selective recognition and robust determination of norfloxacin. BP-PEDOT:PSS was prepared via a simple ultrasonic-assisted liquid-phase exfoliation as an efficient support for use in MIP electrochemical sensors. The imprinted PPy film was deposited onto the surface of BP-PEDOT:PSS via the potentiodynamic technique in the presence of norfloxacin, with the imprinting factor of 3.86 for norfloxacin. The morphologies and microstructures of the sensing materials were investigated using scanning electron microscopy, energy dispersive X-ray spectroscopy, transmission electron microscopy, and Raman spectroscopy. Additionally, parameters including the BP-PEDOT:PSS loading volume, norfloxacin:pyrrole molar ratio, electropolymerization cycles, template removal, solution pH, and time of electrode exposure to the analyte were optimized. Under optimal conditions, the response peak currents of norfloxacin correlated linearly to norfloxacin concentrations from 0.001 to 10 μM, with a limit of detection of 0.25 nM. The prepared imprinted sensor could effectively distinguish norfloxacin from other fluoroquinolone antibiotics with the selectivity coefficients of 5.4–17.3 and maintained stable, robust voltammetric responses for up to two weeks. Moreover, it successfully detected norfloxacin in pharmaceutical formulations and milk samples. Graphical abstract: A novel molecularly imprinted polymer (MIP) voltammetric sensor based on polypyrrole (PPy) imprinted film-bearing poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate-functionalized black phosphorene (BP-PEDOT:PSS) was developed for use in the selective recognition and robust determination of norfloxacin. Image 1 Highlights: MIP film bearing BP-PEDOT:PSS for use in the selective recognition and robust determination of norfloxacin. A fast strategy for template molecule removal combining electrochemical overoxidation and methanol-NaOH elution. A wide linear range (0.001–10 μM) and low LOD of 0.25 nM for norfloxacin detection. Extraordinary selectivity against other fluoroquinolone antibiotics. Stable, robust voltammetric responses for up to two weeks.